Calamoceras sp. nov. (Trichoptera: Calamoceratidae) from the Western Rif area, Morocco - Harrak, Rihab; Alami, Majida El; Hajji, Kamilia; Morse, John C.; Dakki, Mohamed (Zootaxa, 2024)
We describe a new species of the genus Calamoceras which currently has only two species: Calamoceras illiesi Malicky & Kumanski 1974 and Calamoceras marsupus Brauer 1865. We also discuss its ecology by analyzing some biophysical parameters. The larva and the adult of this new species, Calamoceras riffensis sp. nov. have been found by specialists from the Rif region in northwestern Morocco since 1998. All the specimens collected differ from the two known species by conspicuous morphological differences.